TH2.3: Smallholder Farmers Willingness to Pay for Crop Insurance Among Women and Men in Kenya - Waweru, Caroline; Kramer, Berber; Aredo, Samson Dejene (International Food Policy Research Institute, 2022)
Because of increased incidences of drought due to climate change, it is vital that both men and women farmers can manage production risks. Agricultural insurance has been widely promoted to cushion farmers against adverse weather events, yet its uptake remains low, even more so among women. We therefore elicited incentivized measures of willingness to pay (WTP) for various agricultural insurance bundles offered to smallholder farmers within 7 counties in Kenya and analyze how WTP for the various bundles differs between women and men, and how it correlates with the Project-level Women's Empowerment in Agriculture Index (Pro-WEAI). We find that WTP is highest when the insurance product makes payouts in respondents' personal mobile money account, with significantly lower WTP when paid into their spouse's account, or into their savings group (ROSCA)'s account. This is consistent with the finding that control over use of income and autonomy in decision making are two of the main contributors to both men's and women's disempowerment. In conclusion, one of the ways to ensure that agricultural insurance supports women's empowerment is to ensure that insurance contracts purchased by women are registered under their names and payouts are subsequently paid to their accounts, so that they gain control over the use of income from insurance payouts.